PEMETAAN PROBLEMATIKA KOMUNIKASI DALAM AKTIVITAS DAKWAH DI MAJLIS TAKLIM KOTA PEKANBARU - Ginda Ginda; Yefni Yefni (Sosial Budaya, 2016)
This study is intended to find problems of communication in missionary activities in taklim. Da'wah is an activity that can not be separated from communication activities. Even the missionary activities in the broadest sense is the communication itself. From the perspective of science "propaganda" and "communication" departing from efistemologi respectively, but the implementation side there is a meeting point, where propaganda can utilize communication theories to complement the theoretical need for development in the science of propaganda. At this level of study the problems of propaganda in taklim can be done from the perspective komunikasi. Penemuan theories about the problematics of communication in general be part of the problem of propaganda invention, communication problems in taklim, is also a problem of propaganda.